Overexpression of granulocyte-macrophage colony-stimulating factor induces pulmonary granulation tissue formation and fibrosis by induction of transforming growth factor-beta 1 and myofibroblast accumulation. - Xing, Z. (1997)
We have previously reported that transfer to rat lung of the granulocyte-macrophage colony-stimulating factor (GM-CSF) gene leads to high expression of GM-CSF between days 1 and 4 and granulation tissue formation followed by an irreversible fibrotic response starting from day 12 onward. In the current study, we investigated the underlying mechanisms. We found that GM-CSF overexpression did not enhance production of tumor necrosis factor-alpha in a significant manner at any time after GM-CSF gene transfer. However, the content of transforming growth factor-beta 1 in bronchoalveolar lavage fluid was markedly induced at day 4 and appeared to be maximal around day 7 and remained high at day 12. Macrophages purified from bronchoalveolar lavage fluid 7 days after GM-CSF gene transfer spontaneously released significant quantities of transforming growth factor-beta 1 protein in vitro. After peak transforming growth factor-beta 1 production was the emergence of alpha-smooth muscle actin-rich myofibroblasts. Accumulation of these cells was most prominent at day 12 within the granulation tissues and they were still present in fibrotic areas between days 12 and 24 and diminished markedly afterward. Thus, we provide the first in vivo evidence that tumor necrosis factor-alpha may be dissociated from participation in a fibrotic process in the lung and GM-CSF may play a more direct role in pulmonary fibrogenesis at least in part through its capability to induce transforming growth factor-beta 1 in macrophages and the subsequent emergence of myofibroblast phenotypes. This GM-CSF transgene lung model is useful for a stepwise dissection of both cellular and molecular events involved in pulmonary fibrosis.